Firstness, history, place & legitimate claim to place-as-homeland in comparative focus - Roberts, Michael; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2005)
With reference to Sri Lanka, Malaysia, and Australia.
Based on a Feb. 2003 presentation at a conference at the University Kebangsaan Malaysia.
Keywords: Indigenous peoples -- Land tenure; Group identity -- Political aspects; Ethnic relations -- Political aspects; Nationalism